A Passion to Repurpose: Flexibility in the Future. (1st March 2021) - Evans, Martyn
Abstract: Martyn Evans is Creative Director of U+I, which specialises in complex, mixed‐use, community‐focused property development and regeneration projects. He looks at AHMM's engagement with office design, in particular their commercial, spatial reconfiguration, occupancy, newbuild, refurbishment and retrofitting expertise – a terrain within which they are renowned innovators.